Space-time Formations In The South Indian Tamil Popular Film Kannathil Muthamittal - Loganathan, Ramesh; Pillai, Shanthini; Krish, Pramela (Penerbit Universiti Sains Malaysia (USM Press), 2018)
In tandem with the current development of flm scholarships in the area of the world and national cinemas, the paper seeks to examine four scenes from the South Indian Tamil popular flm “Kannathil Muthamittal” (English: A Peck on the Cheek) using a concept derived from Hamid Nafcy’s theorisation of an accented cinema known as the flmmakers’ “preoccupation with the place.” The conception is cinematically expressed through spatial representations of the open, closed and the third spacetime formations. In the accented cinema, space-time formations are cinematic spatial aspects that are employed to produce or reproduce the fundamental “accent” of displacement and deterritorialisation. According to Nafcy, the accent predominantly originates from the flmmakers’ experiences and their artisanal productions and not so much from their accented lingo.